Judicial Transparency: Towards Sustainable Development in Post-Soviet Civil Society - Oksana Khotynska-Nor (Access to Justice in Eastern Europe, 2022)
The processes of transition to democracy that post-Soviet countries underwent in the early 1990s predetermined different directions for their further development. The author presents and proves the hypothesis that in the context of post-Soviet civil society, judicial transparency arose as a response to a social demand at a certain historical moment of crisis of public authority. The idea of transparency in post-Soviet countries appeared only at a certain level of development of political institutions and public law, pointing out the democratic transition of power. At the same time, its emergence established information asymmetry and the poor quality of state institutions of power.